Step
*
1
2
2
2
1
2
of Lemma
add-ipoly-equiv
1. n : ℤ
2. 0 < n
3. ∀p,q:iMonomial() List.
     (||p|| + ||q|| < n - 1 
⇒ ipolynomial-term(add-ipoly(p;q)) ≡ ipolynomial-term(p) (+) ipolynomial-term(q))
4. u : iMonomial()
5. v : iMonomial() List
6. u1 : iMonomial()
7. ¬↑imonomial-le(u1;u)
8. v1 : iMonomial() List
9. ||[u / v]|| + ||[u1 / v1]|| < n
10. ↑imonomial-le(u;u1)
⊢ ipolynomial-term([u / add-ipoly(v;[u1 / v1])]) ≡ ipolynomial-term([u / v]) (+) ipolynomial-term([u1 / v1])
BY
{ (RWW "ipolynomial-term-cons 3" 0 THENA Auto) }
1
1. n : ℤ
2. 0 < n
3. ∀p,q:iMonomial() List.
     (||p|| + ||q|| < n - 1 
⇒ ipolynomial-term(add-ipoly(p;q)) ≡ ipolynomial-term(p) (+) ipolynomial-term(q))
4. u : iMonomial()
5. v : iMonomial() List
6. u1 : iMonomial()
7. ¬↑imonomial-le(u1;u)
8. v1 : iMonomial() List
9. ||[u / v]|| + ||[u1 / v1]|| < n
10. ↑imonomial-le(u;u1)
⊢ imonomial-term(u) (+) ipolynomial-term(v) (+) imonomial-term(u1) (+) ipolynomial-term(v1) ≡ (imonomial-term(u)
                                                                                              (+) ipolynomial-term(v))
  (+) imonomial-term(u1)
  (+) ipolynomial-term(v1)
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  \mforall{}p,q:iMonomial()  List.
          (||p||  +  ||q||  <  n  -  1
          {}\mRightarrow{}  ipolynomial-term(add-ipoly(p;q))  \mequiv{}  ipolynomial-term(p)  (+)  ipolynomial-term(q))
4.  u  :  iMonomial()
5.  v  :  iMonomial()  List
6.  u1  :  iMonomial()
7.  \mneg{}\muparrow{}imonomial-le(u1;u)
8.  v1  :  iMonomial()  List
9.  ||[u  /  v]||  +  ||[u1  /  v1]||  <  n
10.  \muparrow{}imonomial-le(u;u1)
\mvdash{}  ipolynomial-term([u  /  add-ipoly(v;[u1  /  v1])])  \mequiv{}  ipolynomial-term([u  /  v])
    (+)  ipolynomial-term([u1  /  v1])
By
Latex:
(RWW  "ipolynomial-term-cons  3"  0  THENA  Auto)
Home
Index